Removing Nuclear Weapons from Turkey. Issue 5 (2nd September 2016) - Fitzpatrick, Mark
Abstract : Following the 15 July coup attempt, the American nuclear weapons in Turkey may now be the first of those stationed on NATO territory to be withdrawn.